Improving the efficiency of the UV detector by increasing the optical sensitivity - الطيف عبد الحسين خضير (University of Thi-Qar Journal of Science, 2014)
In this work, (SnO2) thin films were prepared by thermal chemical spray pyrolysis technique using mixture of Tin chloride hydrate ((SnCl2.2H2O)) with molar concentration of (0.1M) at glass substrate temperature of 400 ˚C. X-ray diffraction analysis indicated that all the prepared films have polycrystalline structure. Optical properties of the films were determined by studying the ultraviolet spectrum which include transmittance , absorptance , absorption coefficient and energy gap which have a value of (3.65eV) before annealing and about (3.8 eV) after annealing .The spectral responsivity of the uncoated detector in UV range was (0.15 A/W) .The photo response enhancement of the photoconductive detector is improved by coating (SnO2) films with 200nm (PMMA) polymer .The results show that the responsivity is increased more than responsivity of the uncoated (SnO2) and it reaches (1.62 A/W) at (385nm)and at (10V) bias voltage.